Pemberdayaan Ekonomi Masyarakat Melalui Kelompok Usaha Bersama (KUBE) - Lisda Dzulhijjah; Deden Sumpena; Ali Azis (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2020)
This paper aims to find out the strengthening, protection, support and maintenance of the economic community carried out by joint business groups and the results of community economic empowerment through joint business groups. This research uses descriptive method with qualitative data types. Research subjects are managers, members, and families of members of a joint venture group. Data collection uses observation, interview, and document study techniques. Data analysis in this study is interpretation or interpretation of logic by means of reducing data, presenting data, verifying and drawing conclusions that are related to the context of the development of Islamic society. The results of the research analysis showed that the strengthening, protection, support, and maintenance carried out by the joint venture group succeeded in empowering the community's economy by achieving an improved community economy, more active social activities, and a more creative and independent community.